RAWUL: A new ubiquitin-like domain in PRC1 Ring finger proteins that unveils putative plant and worm PRC1 orthologs - Sanchez-Pulido, Luis; Devos, Damien; Calonje, Myriam (BMC genomics, 2008)
Polycomb group (PcG) proteins are a set of chromatin-modifying proteins that play a key role in epigenetic gene regulation. The PcG proteins form large multiprotein complexes with different activities. The two best-characterized PcG complexes are the PcG repressive complex 1 (PRC1) and 2 (PRC2) that respectively possess histone 2A lysine 119 E3 ubiquitin ligase and histone 3 lysine 27 methyltransferase activities. While PRC2-like complexes are conserved throughout the eukaryotic kingdoms, PRC1-like complexes have only been described in Drosophila and vertebrates. Since both complexes are required for the gene silencing mechanism in Drosophila and vertebrates, how PRC1 function is realized in organisms that apparently lack PRC1 such as plants, is so far unknown. In vertebrates, PRC1 includes three proteins, Ring1B, Ring1A, and Bmi-1 that form an E3 ubiquitin ligase complex. These PRC1 proteins have an N-terminally located Ring finger domain associated to a poorly characterized conserved C-terminal region.